THE FORMATION AND INFLUENCE OF THE MILITARY ARCHITECTURE IN OMAN DURING AL-YA'ARIBA PERIOD (1034-1162 AH/1624–1749 AD) - Naima Benkari (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Despite its richness, the research corpus published about Islamic architecture presents some discontinuities in the knowledge of the architecture in the lands ruled by Muslims. Similarly, the dynamics of influence that might have operated between the